Factors affecting doctor's recommendation for mobile health services. (September 2022) - Hu, Xiaojing; Fang, Hongjun; Wang, Ping
Objective: As a new medical service mode, the value of mobile health (mHealth） services has received increasing attention and recognition. However, compared with the owners of mobile devices, the user scale of mHealth services is still small. It is well known that doctors' recommendations have an important impact on what kind of medical service patients choose. To explore the key factors affecting doctors' recommendation of mHealth services to patients, and to provide countermeasures for mHealth service providers and hospital managers, so as to promote doctors to recommend mHealth services to more patients. Methods: Through literature review, expert consultation and pre-test, a questionnaire including 22 questions was designed, and 114 valid questionnaires were collected by online research. Net Promoter Score (NPS) was used to evaluate doctors' recommendation willingness, and multivariate logistics analysis was used to evaluate the key factors affecting doctors' recommendation willingness. Results: The NPS of doctors was 6.06%, among which the recommenders, neutrals and critics accounted for 29.56%, 46.96% and 23.48%, respectively. The attitude towards mHealth services and whether they pay attention to and/or are willing to try new technologies are the key factors affecting the doctors' recommendation, and the usefulness for patients most often emphasized by mHealth service providers to doctors does not affect doctors' recommendation willingness. In addition, whether mHealth services can help doctors establish personal brands may be a potential factor to enhance doctors' recommendation willingness. Conclusion: In order to improve the recommendation willingness of doctors, mHealth service providers and hospital managers should focus on doctors who have a positive attitude towards mHealth services and are highly innovative (which often means younger and lower professional levels). At the same time, they should think about how to use mHealth services to help doctors establish personal brands in the future.